The Dark Matter of World Politics: System Trust, Summits, and State Personhood. (2022) - Ku, Minseon; Mitzen, Jennifer
Abstract: International relations theory has had a trust revival, with scholars focusing on how trust can enhance interpersonal cooperation attempts between leaders. We propose there is another type of trust at play in world politics. International system trust is a feeling of confidence in the international social order, which is indexed especially by trust in its central unit, state persons. System trust anchors ontological security, and its presence is an unstated assumption of the international relations trust scholarship. In this paper we conceptualize system trust. We illuminate its presence by flagging the production of state personhood in a familiar case in international relations trust scholarship, the 1985 Geneva Summit between Reagan and Gorbachev. Interpersonal and system trust perspectives highlight different aspects of the same summit. The juxtaposition suggests new lines of research into the production of state persons in diplomacy, the relationship between interpersonal and system trust, and the impact of the rise of personalistic/patrimonial leadership on diplomacy and international order.